Grain Sorghum Response to Hybrid, Row Spacing, and Plant Populations along the Upper Texas Gulf Coast - Dan D. Fromme; Carlos J. Fernandez; W. James Grichar; Rick L. Jahn (International Journal of Agronomy)
Grain sorghum (Sorghum bicolor L. Moench) along the upper Texas Gulf Coast is planted at different row spacings, plant populations, and hybrids according to grower preference and location. This study was conducted over a 3-year period (2001 to 2003) to determine the combination of hybrid, row spacing, and plant population on yield and net return per hectare. Below average rainfall for May and June occurred in 2002 and 2003 which resulted in lower yields than 2001. In 2001 and 2003, Dekalb (DK) 54 generally produced higher yields than Asgrow (A) 571 on the 51 cm row spacing. In 2002, no differences in grain sorghum yield were found when comparing both hybrids, plant populations, or row spacing with the exception of A 571 planted at 148,000 plants/ha on 102 cm centers which resulted in a yield reduction of at least 25%. When net returns were compared regardless of year or rainfall received, net dollar value per hectare tended to be higher for the 51 cm row spacing, especially with A 571.